The Effect of Strategic Agility, Entrepreneurial Leadership and Innovation Capability on SME’s Performance - Saputra, Rahmadani; Nasution, Yasmine (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2023)
Small and Medium Enterprises is one of the business sectors that has the most influence on the growth of the national economy. Some Small and Medium Enterprises have succeeded in developing but not a few have failed, for example due to the economic crisis. The survival and development of Small and Medium Enterprises is influenced by various factors. The factor to be seen in this research is the role of Strategic Agility, Entrepreneurial Leadership, and Innovation Capability in developing the performance of Small and Medium Enterprises. The research method used in this study is quantitative with the SEM-PLS method to analyze these three concepts on the performance of Small and Medium Enterprises. This research focuses more on the role of Strategic Agility, Entrepreneurial Leadership, and Innovation Capability on SME Performance so that they can grow and develop.